Botanical Drug Extracts Combined With Biomaterial Carriers for Osteoarthritis Cartilage Degeneration Treatment: A Review of 10 Years of Research - Mu, Panyun; Feng, Jie; Hu, Yimei; Xiong, Feng; Ma, Xu; Tian, Linling (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is a long-term chronic arthrosis disease, usually characterized by pain, swelling, joint stiffness, reduced range of motion and other clinical manifestations, and even disability in severe cases. OA is characterized by degeneration of cartilage. However, due to the special physiological structure of cartilage, once damaged, it is unable to repair itself, which is one of the challenges of treating OA clinically. Abundant researches have reported the application of cartilage tissue engineering in OA cartilage repair. Cell implantation scaffold has its unique advantages when applied to cartilage. However, in vitro culture, both bone marrow mesenchymal stem cells and chondrocytes will face problems such as cell senescence, death and dedifferentiation. Herbal remedies for osteoarthritis have a long history in many countries in Asia. In fact, herbal monomers have great potential in anti-inflammatory, antioxidant, anti-aging and other aspects, and many studies have confirmed their effects. Herbal monomer combined with cartilage tissue engineering has attracted more and more attention in recent years. In this review, we need to explain in detail how cartilage tissue engineering materials and herbal monomers play a role in cartilage repair, as well as the current research status.